Oxidation of isochemical FeS2 (marcasite-pyrite) by Acidithiobacillus thiooxidans and Acidithiobacillus ferrooxidans - Garcia, Oswaldo; Bigham, Jerry M.; Tuovinen, I. H. (Elsevier B.V., 2007)
A research-grade mineral sample that contained marcasite and pyrite (FeS2) was subjected to the oxidation by Acidithiobacillus ferrooxidans and Acidithiobacillus thiooxidans. Oxidation of FeS2 by A. ferrooxidans produced acid, and the redox potential increased with sulfide dissolution and the oxidation of Fe2+. jarosite was detected in solids from spent cultures. Preferential oxidation of either mineral was not consistently observed across all treatments. Neither iron sulfide was oxidized by A. thiooxidans. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: Acidithiobacillus; bioleaching; marcasite; pyrite